Problem-based learning: Generates higher-order thinking skills of tenth graders in ecosystem concept - Siti Ramdiah; H. Abidinsyah; Ria Mayasari (University of Muhammadiyah Malang, 2018)
This study aimed to determine the effect of Problem-Based Learning (PBL) model on tenth grade students’ higher-order thinking skills (HOTS) in ecosystem concept. The design of this study was quasi experimental research with